Synthesis of a Carbamazepine Derivative as Antibacterial Agent - Figueroa-Valverde, Lauro; Díaz-Cedillo, Francisco; Garcia-Cervera, Elodia; E.M. Pool-Gómez, Jose; Cardeña-Arredondo, Carlos (Asian Journal of Chemistry, 2011)
In this work, the carbamazepine derivative (N-[(1E)-1-methylpent-1-enyl]-N-phenyl-5Hdibenzo[ b,f]azepine-5-carboxamide) was synthesized using the three-component system (carbamazepine, benzaldehyde and 2-hexyne) in presence of cupric chloride as catalyst. Additionally, the antibacterial activity of carbamazepine derivative was evaluated in vitro on S. aureus and E. coli using the NCCLS method with some modifications. To delineate the structural chemical requirements of the compound N-[(1E)-1-methylpent-1-enyl]-N-phenyl-5Hdibenzo[ b,f]azepine-5-carboxamide as antibacterial agents on S. aureus and E. coli, other chemical parameters such as the descriptors log P, p, Rm, Vm, Pc and St were calculated. The results showed that bacterial growth of the microorganisms studied was inhibited by the carbamazepine derivative in a dose-dependent manner. Other results showed an increase in log P, p, Rm, Vm, Pc and St values in comparison with carbamazepine. These data suggest that functional groups involved in the structure of the studied compound are specific for its antibacterial activity.